Adjustment of Subthalamic Deep Brain Stimulation Parameters Improves Wheeze and Dyspnea in Parkinson's Disease - Komiya, Hiroyasu; Kimura, Katsuo; Kishida, Hitaru; Kawasaki, Takashi; Hamada, Koichi; Koizumi, Hiroyuki; Ueda, Naohisa; Tanaka, Fumiaki (Frontiers in Neurology, 2019)
Subthalamic nucleus deep brain stimulation (STN-DBS) is an effective treatment for motor features in Parkinson’s disease (PD). We present the case of a 56-year-old man with a 17-year history of PD. He underwent bilateral STN-DBS at the age of 51 years because of troublesome dyskinesia and wearing off. His motor features dramatically improved after the operation; however, he developed dysarthria and a refractory wheeze associated with dyspnea due to abnormal hyperadduction of the false vocal fold. By adjusting the stimulation site of STN, his severe wheeze, which was considered to be the result of the unfavorable spread of current to the corticobulbar tract, was significantly improved. This report provides concrete evidence that wheezing is caused by hyperadduction of the false vocal fold as an adverse effect of STN-DBS and can be reversed by adjusting the stimulation site for STN-DBS.